Pan-cancer analyses reveal multi-omics and clinical characteristics of RIO kinase 2 in cancer - Li, Kexin; Zou, Jiahua; Yan, Haizhao; Li, Yuqing; Li, Man-Mei; Liu, Zhong (Frontiers in Chemistry, 2022)
RIO kinase 2 has emerged as a critical kinase for ribosome maturation, and recently it has also been found to play a fundamental role in cancer, being involved in the occurrence and progression of glioblastoma, liver cancer, prostate cancer, non-small cell lung cancer, and acute myeloid leukemia. However, our knowledge in this regard is fragmented and limited and it is difficult to determine the exact role of RIO kinase 2 in tumors. Here, we conducted an integrated pan-cancer analysis comprising 33 cancer-types to determine the function of RIO kinase 2 in malignancies. The results show that RIO kinase 2 is highly expressed in all types of cancer and is significantly associated with tumor survival, metastasis, and immune cell infiltration. Moreover, RIO kinase 2 alteration via DNA methylation, and protein phosphorylation are involved in tumorigenesis. In summary, RIO kinase two serves as a promising target for the identification of cancer and increases our understanding of tumorigenesis and cancer progression and enhancing the ultimate goal of improved treatment for these diseases.